2016
DOI: 10.1097/gox.0000000000001060
|View full text |Cite
|
Sign up to set email alerts
|

Mesh Sutured Repairs of Abdominal Wall Defects

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…The conceptual underpinnings that the distribution of forces is critical to the creation of a durable laparotomy closure had led to a completely different surgical technique for high tension internal closures [35]. Termed a ''mesh sutured repair,'' strips of macroporous uncoated polypropylene mesh (Soft Prolene Mesh, Ethicon, Somerville, NJ) 2-cm wide are cut along the blue lines of the mesh.…”
Section: Mesh Sutured Repairsmentioning
confidence: 99%
“…The conceptual underpinnings that the distribution of forces is critical to the creation of a durable laparotomy closure had led to a completely different surgical technique for high tension internal closures [35]. Termed a ''mesh sutured repair,'' strips of macroporous uncoated polypropylene mesh (Soft Prolene Mesh, Ethicon, Somerville, NJ) 2-cm wide are cut along the blue lines of the mesh.…”
Section: Mesh Sutured Repairsmentioning
confidence: 99%
“…As previously described, 3 a light-weight, macroporous, uncoated polypropylene mesh (PROLENE ® Soft Prolene Mesh, Ethicon, Somerville, NJ) 10  14 inches in size (30.5 cm  35.6 cm) was cut along the blue lines into 2 cm wide pieces in order to fabricate mesh strips in this off-label use of the product. Subcutaneous tissue was elevated off of the abdominal wall only as necessary in order to achieve a 1 cm wide bite of unscarred abdominal wall.…”
Section: Mesh Sutured Techniquementioning
confidence: 99%
“…We recently described a technique called a "mesh sutured repair" using strips of light-weight macroporous polypropylene mesh passed through the abdominal wall and tied like sutures to achieve closure. 3 Mesh sutured repairs aim to capitalize on the biomechanical benefits of force distribution to reduce tearing, while minimizing the drawbacks of the total volume of implanted material and the required tissue dissection. Pre-clinical studies demonstrated the biomechanical benefits over conventional suture repair, with decreased suture pull-through and increased early tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Methods described for this study include the use of bone anchors 43 , 44 , 48 , 49 and direct suture fixation. 50 The senior author has developed a method of hernia repair using 2-cm strips of macroporous polypropylene mesh 51 , 52 that are used as sutures. A strip of mesh has the advantage of a larger surface area and, thus, a greater force distribution across the closure when compared with a single strand of suture.…”
Section: Introductionmentioning
confidence: 99%